(untitled) (Nepal Journal of Neuroscience, 2026)
Background: Transsphenoidal surgery (TSS) is the primary treatment for pituitary tumors. Until 2016, microscopic sublabial TSS was performed for tumors of the pituitary gland. We took an X-ray at the time of operation to localize the sella floor and then used the microscope. Once we obtained the 3D endoscope, all surgeries are performed with the endoscope except for giant tumors requiring craniotomy. Objective: To assess the clinical features, tumor types, and surgical outcomes of endoscopic pituitary surgery over 10 years and compare them against our previously microscopic experience. Methods: We reviewed a total of 267 patients who underwent pituitary surgery between April 2016 and March 2026. Data were analyzed on age, sex, symptoms, tumor type, Knosp grading, and extent of resection. Before 2016, surgery was done with a microscope; after that, we used an endoscope. Results: There were 120 males (45%) and 147 females (55%) with a mean age of 34 years. Headache was the most common (32%), followed by visual problems (24%) and amenorrhea/galactorrhea (22%). Acromegaly was present in 11%, and pituitary apoplexy in 6%. Non-functioning tumors (48%), prolactinomas 25%, and GH-secreting 22% were most common. Most tumors were invasive: Knosp 3A (39%), 3B (40%), and 4 (11%). With an endoscope, complete removal was achieved in 88% of cases. Under the microscope (until 2016), it was 92%. The microscopic approach provides a slightly better visualization at the extent of the resection. Endoscopic surgery has shorter operative times, less blood loss, and better visualization during surgery. Conclusion: Endoscopic pituitary surgery is safe and efficacious. Complete removal is a bit less efficient than the microscope, endoscope has clear advantages: (1) Less time, (2) less bleeding, (3) better intraoperative view. It is now our go-to method of treating most pituitary tumors.